2021
DOI: 10.23937/2474-3658/1510194
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic Survey of HBV, HCV and HIV Infections in a Pregnant Women Population in Central Nigeria: A Cross-Sectional Study

Abstract: Parallel and overlapping of HBV, HCV and HIV infections in pregnant women is a major public health problem. In this cross-sectional study, we evaluated the parallel and overlapping infections of HBV, HCV and HIV among pregnant women population in Keffi, Central Nigeria between June through August 2019. Four hundred (400) women blood specimens were collected from major Hospitals in Keffi for the study after informed consent and ethical approval were retrieved and a structured questionnaire was administered to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
3
1
Order By: Relevance
“…Ranges of 2% to 15% prevalence of HBV among pregnant women have been reported in Nigeria [24]. In contrast to our findings on similar research studies carried out in other part of Nigeria, the following reported a high prevalence rate of HBV infection (19.8%), among pregnant women attending antenatal care clinic at Federal Medical Center, Keffi, North-Central Nigeria 16.6% among patients attending a tertiary hospital in Jalingo at Ibadan 16.3% and 14.6% in Bauchi, North-Eastern Nigeria [19,[25][26][27]. A pooled prevalence of 13.6% for adults and 11.5% for children from another study conducted in Nigeria [28].…”
Section: Discussioncontrasting
confidence: 69%
“…Ranges of 2% to 15% prevalence of HBV among pregnant women have been reported in Nigeria [24]. In contrast to our findings on similar research studies carried out in other part of Nigeria, the following reported a high prevalence rate of HBV infection (19.8%), among pregnant women attending antenatal care clinic at Federal Medical Center, Keffi, North-Central Nigeria 16.6% among patients attending a tertiary hospital in Jalingo at Ibadan 16.3% and 14.6% in Bauchi, North-Eastern Nigeria [19,[25][26][27]. A pooled prevalence of 13.6% for adults and 11.5% for children from another study conducted in Nigeria [28].…”
Section: Discussioncontrasting
confidence: 69%
“…Similarly, the combined HIV/HBV/HCV prevalence reported byShrestha et al (2021) in a systematic review study of Nepal from 1990 to 2020 was 1.3%. In Eastern Nepal, 2.53% of cases of HIV/HBV/HCV triple infections were reported by Shrestha et al in 2022.It is essential to note the increased prevalence of HBV and HCV dual infection in this study compared to prior studies(Oti et al, 2021). Furthermore, these studies have shown that triple HIV/HBV/HCV infections or dual HIV/HBV/HCV infections are the most prevalent.…”
mentioning
confidence: 57%
“…To the best of our knowledge, there is no information on the relationship between CD4 When compared to the WHO norm, we discovered that the overlapping infections of HIV/HBV/Plasmodium falciparum, HIV/HCV/Plasmodium falciparum, HIV/HBV/HCV, and HIV/HBV/HCV/Plasmodium falciparum were 2.9%, 1.9%, 1.9%, and 1.0%, respectively (Oti et al, 2021). Chronic HCV carriers' interactions with malaria parasites may prevent the latter from spreading, which may aid in developing novel malaria treatment strategies (Gasim & Adam, 2015).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation